City and Regional Planning - LeGates, Richard T., author 257845 (New York, NY : Routledge, 2023)
"City and Regional Planning provides a clearly written and lavishly illustrated overview of the theory and practice of city and regional planning. With material on the globalization and the world city system and provides examples from other countries, the book has been written with the needs of readers worldwide who seek an overview of city and regional planning. Chapters cover the history of cities and city and regional planning, urban design and placemaking, comprehensive plans, planning politics and plan implementation, planning vision, and environmental, transportation, and housing planning. The book pays special attention to diversity, social justice, and collaborative planning. Topics include current practice in resilience, transit-oriented development, complexity in planning, spatial equity, globalization, and advances in planning methods. It is aimed at U.S. graduate and undergraduate city and regional planning, geography, urban design, urban studies, civil engineering and other students and practitioners. It includes extensive material on current practice in planning for climate change. Each chapter includes a case study, a biography of an important planner, lists of concepts and important people and an list of books, article, videos, and other suggestions for further learning"-- Provided by publisher.